The Influence of Career Development, Mutations, and Information Technology on Employee Performance at the Center of Statistics Agency in Bangka Belitung Islands Province - Julianti, Laravita Prihastina; Reniati, Reniati; Lestari, Etty Puji (International Journal Labs, 2023)
The success of an agency in achieving its goals is not only determined by the complete organizational structure or structure, but is also influenced by the factor of placing individuals in the right positions according to their abilities and expertise, which among all these individuals is a form of work partner that can determine the success or failure of an activity within the agency. From 2014 to 2018 employee mutations within the BPS Bangka Belitung Islands Province have continued to increase. In addition, optimizing employee performance in providing services certainly requires a breakthrough in the field of technological innovation to improve individual and organizational performance. One of them is the use of information technology which is a means of supporting/encouraging the organization in achieving organizational goals. Researchers want to find out more about the effect of career development, mutation and information technology on employee performance at BPS Bangka Belitung Islands Province. This study aims to see the effect of career development, mutation and information technology on employee performance at the Central Bureau of Statistics (BPS) of the Bangka Belitung Islands Province, either partially or jointly. This type of research is causal quantitative research using survey methods. The subjects and research locations were 60 BPS employees of the Bangka Belitung Islands Province. Before obtaining the best equation, the validity and reliability of the data must be guaranteed from the question items submitted by using data quality tests which include validity tests, reliability tests, and classical assumption tests (normality tests, multicollinearity tests, and heteroscedasticity tests). Data analysis used partial test (t test), simultaneous test (F test), multiple regression statistical tests and the coefficient of determination (Adjusted R Square). Validity and reliability tests were carried out to see whether the research questionnaire was valid or not. The t test was conducted to determine the effect of each independent variable on the dependent variable while the F test was conducted to determine whether the independent variables simultaneously had a significant effect on the dependent variable. The results of the study show that there is an influence of career development, mutation, and information technology on employee performance at the Central Bureau of Statistics (BPS) of the Bangka Belitung Islands Province. Career development, transfer, and information technology successively have an influence of 15.1 percent, 17.0 percent, and 17.4 percent on the performance of BPS employees in the Bangka Belitung Islands Province. While the three variables together give an effect of 32.5 percent. There is the influence of career development, mutation, and information technology together on the performance of BPS employees of the Bangka Belitung Islands Province.